Development Of A Multicomponents Degradable Plastics, Through The Combination Of The Sago Starch And Polyethylene/poly (ε-Caprolactone) Blends - Lim, Wei Lee (2007)
In this research, sago starch (SS), poly(ε-caprolactone) (PCL) were incorporated into low density polyethylene (LDPE).